2016
DOI: 10.17352/gje.000001
|View full text |Cite
|
Sign up to set email alerts
|

Managing Large Herbivores in Protected Areas

Abstract: By nature of their size, grouping behaviour, and central position within most trophic webs, large terrestrial herbivores --namely ungulates and elephants --tend to be both keystone and umbrella species. Their proportionately large impacts on ecosystems extend both top-down (i.e. regulation of vegetation), but also bottom up (regulated their predators). For these reasons, as well as their cultural and economic importance to humans around the world, large herbivores are among the most heavily managed species in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 88 publications
(118 reference statements)
0
3
0
Order By: Relevance
“…Large herbivores act as both keystone species and umbrella species in ecosystems and should be managed for the maintenance and restoration of biodiversity (Found 2016). The results of this study based on camera trap data revealed that, from the 6 large herbivorous species studied, the highest abundance of large herbivorous species in the KYNP were gaur, followed by wild boar, sambar deer, Asian elephant, northern red muntjac and lesser oriental chevrotain, in order.…”
Section: Discussionmentioning
confidence: 74%
“…Large herbivores act as both keystone species and umbrella species in ecosystems and should be managed for the maintenance and restoration of biodiversity (Found 2016). The results of this study based on camera trap data revealed that, from the 6 large herbivorous species studied, the highest abundance of large herbivorous species in the KYNP were gaur, followed by wild boar, sambar deer, Asian elephant, northern red muntjac and lesser oriental chevrotain, in order.…”
Section: Discussionmentioning
confidence: 74%
“…Recovery of populations of large mammals in Europe is beyond doubt [2,7,10,79]. As for ungulates, a lack of a common strategy for their management [7] requires unification, at least in protected territories [9,80].…”
Section: Moose-related Problems: Why Is Management Necessary?mentioning
confidence: 99%
“…Wild caprines (subfamily Caprinae), as large herbivores, are keystone and umbrella species of mountain habitats (Found 2016), as well as valuable game species. In addition, they represent a potential source of new genetic material for improving livestock or to ensure its adaptation to less productive conditions.…”
Section: Introductionmentioning
confidence: 99%